La necropsia médico legal y la identificación del cadáver en delitos de homicidio en la investigación criminal (2014)
The summary indicates , techniques and procedures that have the coroner at necropsy , and identification of the corpse, as a forensic expert is usually the first that provides solid evidence that may become probative evidence . In addressing an alleged made criminal act such as murder of a taxi driver found a place on the route Melgar Girardot with sharps wounds made by sharp objects or tip and which is applied mechanical force to cause injury to the body of the victim , it is important try , from wounds, rebuild angles of some important elements to determine the possible position , victim or perpetrator, or the type of weapon used . The medical examiner must prove that the injury or the set of his injuries were fatal ; if they are several , it is necessary to determine the severity of each and to establish which together led to the death, shall establish a working hypothesis as a guide. The hypothesis may be varied or disposed of in so far as the description proceeds of injuries and necropsy. The doctor examines the significance of the information collected at the scene of the events and provides a hypothesis. By this stage deals with forensic investigation , which analyzes the victim's body for clues to help clarify the death so that the rational study of the work that carries the medical examiner , autopsy and identification of the victim they can provide information about the alleged shooter in the assigned case and the identification of the weapon